Evaluation of Dietary Energy and Protein Requirements of an Improved Backyard Chicken Variety (Rajasri) in its Juvenile Phase - Deepak, N.; Preetam, V. C.; Rajkumar, U.; Prakash, M. Gnana; Alexander, G. (Indian Journal of Animal Nutrition, 2017)
A study was conducted to evaluate the dietary energy and protein requirements of an improved backyard chicken variety (Rajasri) during its juvenile phase (0-8 weeks of age). Day old Rajasri chicks (n=360) were randomly distributed into 9 groups of 5 replicates with 8 chicks per replicate. They were fed diets with three ME levels (2400 kcal, 2600 kcal and 2800 kcal ME/kg) and three CP levels (16, 18 and 20%) in a 3 Ã— 3 factorial design. The body weight gain of chicks fed 2600 and 2800 kcal ME/kg diets was higher (P<0.05) than those fed 2400 kcal ME/kg and increased (P<0.001) with increasing levels of CP in diet. Feed intake was higher (P<0.05) in groups fed 2400 and 2600 kcal ME/kg when compared to 2800 kcal ME/kg fed groups and was not influenced by different levels of CP in the diet. Feed conversion ratio of groups fed 2600 and 2800 kcal ME/kg was better than those fed 2400 kcal ME/kg and improved with increasing levels of CP. Protein retention was better (P<0.05) in groups fed diets having 2600 and 2800 kcal ME/kg and was not influenced by different CP levels or ME and CP interactions. Energy retention was similar in different groups. Serum total cholesterol level was higher (P<0.001) in chicks fed diets containing 2400 kcal ME/kg and serum total protein level was similar and not influenced by different levels of ME, CP and their interactions. Hence, provision of diet containing 2600 kcal ME/kg and 20% CP would be ideal for eliciting optimum growth in Rajasri chicks during juvenile phase.